"Not All Visual Media Are Helpful": An Optimal Instructional Medium for Effective Online Learning. (September 2014) - Lehtola, Whitney I.; Gemignani, Stephen M.; Sutherland, Jared T.; Jeon, Myounghoon
With an increasing online learning population, many questions are arising as to the best way of teaching online. A number of common methods incorporate visual formats into the teaching method. Currently, an area lacking in research is which visual format communicates material most effectively to students. In this study, the focus was on discovering whether it is more effective to use an audio-pictorial video rather than an audio-text video. Sixteen undergraduates participated in this study. Each group was exposed to one of three test conditions: audio-video, audio-text, or audio-only (control). The participants were then asked to complete the task of making a unique paper airplane. As our hypothesis, the results showed that the audio-video group had significantly higher completion rates for the task than the other two groups, which showed no difference from each other. Results are discussed in terms of cognitive load theory and multiple resources theory, and a practical recommendation is provided recommending the use of a live audio-video format to teach students online.